Measurements of field enhancement introduced by a local electrode. - Huang, M; Cerezo, A; Clifton, P; Smith, G (2001)
Direct measurements of field enhancement introduced by a local electrode have been carried out on a scanning atom probe (SAP). The results show that an enhancement factor of more than 2 can be obtained simply by reducing the specimen-to-electrode distance from 1.5 mm to 10 microm. Further enhancement can be achieved if the electrode has a smaller aperture. This suggests that a specimen with tip radius of approximately 200 nm, which usually is too blunt to be analysed in a standard atom probe, could now be analysed by SAP. The capability of analysing blunt tips will expand the applicability of SAP to a much broader range of materials.